VILLAGE GOVERNMENTS CAPACITY CHALLENGES FACING HINDRANCES TO IMPLEMENTATION OF THE RECOGNITION PRINCIPLE IN KOLILANANG VILLAGE, EAST FLORES DISTRICT IN 2022 - Yohana Fransiska Medho; Yosef Dionisius Lamawuran; Marianus Kleden; Kristianus Molan; Veronika Ina Asa Boro; Frans Bapa Tokan (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
The principle of recognition not only corroborates and develops the unique tradition of running the village, but also reinvigorates the village to make innovations and rearrangements of its administration based on autochthonous autonomy and decentralization-based local government. This research aims to explore the capacity of village administration to implement the principle of recognition and to reveal impediments being faced, also to contribute to strengthening local capacity for solving community problems. The methods used in this research are qualitative and descriptive where data were collected through in-depth interviews and observations. The result shows that the village administration and the village consultative body both collectively and individually lack the capacity to implement the recognition principles. The inability to implement the recognition principle is caused by poor human resources of both the village administration personnel and the village consultative body. Consequently, there are no creative ideas set forth by the village administration or by the village consultative body as well as by the villagers as a whole to formulate innovative development programs or culture-based village regulations. Therefore, we need to implement capacity-building programs through training, technical assistance, socialization of regulations and well-scheduled sustainable apprenticeship in order for the village administration to design innovative development programs in accordance with the local needs and uniqueness of the village.